The surgical management of NCAA Division 1 college football injuries post COVID-19: a single institution retrospective review - Cohen, J. L.; Cade, W. H.; Harrah, T. C.; Costello, J. P.; Kaplan, L. D. (The Journal of Strength and Conditioning Research, 2024)
The unprecedented COVID-19 pandemic had a significant impact on college football operations, including athletes' training regimens. As a result of these changes, concern for increased injury susceptibility post COVID-19 regulations has become a point of discussion. The current study sought to evaluate the incidence of surgical injury among NCAA Division 1 college football players at the authors' institution during the first full season after start of the COVID-19 pandemic compared with previous years. Retrospective chart review was performed for all players who sustained injuries requiring surgery while a member of the NCAA Division 1 football program during the 2009-2021 seasons. A p-value of =0.05 was used to determine significance. A total of 23 surgical injuries occurred in 22 players during the 2021 season compared with 121 in 118 players in the 12 previous seasons combined (p = 0.0178; RR = 1.47). There was a significant increase in shoulder injuries (n = 13 vs. n = 31; p = <0.0001; RR = 3.05) and specifically a significant increase in labral tears (n = 10 vs. n = 30; p = 0.0003; RR = 2.74). No difference was seen in knee injuries (n = 10 vs. n = 77; p = 0.27; RR = 1.35) and specifically no difference in anterior cruciate ligament injuries (n = 3 vs. n = 31; p = 0.77; RR = 1.17). This phenomenon is multifactorial in nature, but alterations to players' training and preparations because of the COVID-19 pandemic likely resulted in suboptimal conditioning, leading to the increased incidence of surgical injuries emphasizing the importance of adequate strength training and conditioning.